2011
DOI: 10.1186/1758-5996-3-26
|View full text |Cite
|
Sign up to set email alerts
|

Depression, glycemic control and type 2 diabetes

Abstract: BackgroundComorbid depression in diabetes has been suggested as one of the possible causes of an inadequate glycemic control. The purpose of this study was to investigate the association between major depression and the glycemic control of type 2 diabetes mellitus (T2DM).MethodsSeventy T2DM patients were evaluated. They underwent a psychiatric examination using the following instruments: Structured Clinical Interview for DSM-IV and Beck Depression Inventory. The diabetes status was assessed in the short-term (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
7
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 21 publications
6
62
7
4
Order By: Relevance
“…Similarly, another Brazilian study found a prevalence of 18.6% in individuals with T2DM. 18 Similar results were reported in a recent meta-analysis involving more than one hundred thousand participants, which revealed that individuals with T2DM have a 24% higher risk of developing depression, 3 consistent with the results demonstrated in this sample: diabetes is a risk factor for depression.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Similarly, another Brazilian study found a prevalence of 18.6% in individuals with T2DM. 18 Similar results were reported in a recent meta-analysis involving more than one hundred thousand participants, which revealed that individuals with T2DM have a 24% higher risk of developing depression, 3 consistent with the results demonstrated in this sample: diabetes is a risk factor for depression.…”
Section: Resultssupporting
confidence: 79%
“…20 Other authors also reported that patients with T2DM and depression have higher glycated hemoglobin levels compared to people without depression. 18 However, in this study, glycated hemoglobin levels were not associated with the presence of depression, in contrast to most of the evidence from the literature. Another study also previously suggested that blood glucose levels tend to be higher in depressed individuals, despite the lack of significant differences according to the presence of depression.…”
Section: Resultscontrasting
confidence: 56%
“…There are several cross‐sectional studies reporting that depression is a factor associated with poor glycemic control among patients with T2D (Lustman et al ., 2000; Lustman and Clouse, 2005; Papelbaum et al ., 2011; Zhang et al ., 2014). Our results are consistent with these findings even after controlling for a large list of potential confounders; our hierarchical approach is reassuring, suggesting that the impact of covariates is not considerable in the proposed association as estimates remain roughly constant in the different models.…”
Section: Discussionmentioning
confidence: 99%
“…У про-спективному дослідженні, проведеному серед 4117 пацієнтів із ЦД, було встановлено, що наяв-ність депресії та тяжкість проявів були пов'язані з порушенням самоконтролю та недотриманням прийому антидіабетичних препаратів (відношен-ня шансів (ВШ) = 1,98; довірчий інтервал (ДІ) 1,31-29,8; р < 0,001), наявністю артеріальної гі-пертензії (ВШ = 2,06; ДІ 1,47-2,88; р < 0,001) і рівнем показників ліпопротеїнів низької щіль-ності (ВШ = 2,43; ДІ 1,19-4,97; р < 0,01) [6]. Де-які дослідження показали значно вищий середній рівень глікованого гемоглобіну (HbA1c) в групі депресії порівняно з пацієнтами без депресив-них проявів [7,8]. У дослідженні 225 пацієн-тів, що включало 75 пацієнтів із депресивними розладами та 150 осіб контрольної групи, було знайдено позитивний взаємозв'язок між депре-сивними проявами та когнітивними порушення-ми [9].…”
Section: том 13 № 1 2017unclassified